2021
DOI: 10.25115/eea.v39i12.6022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Product Knowledge and Influence of Society on Investment Intention of Stock Investors with Perceived Risk as Mediation

Abstract: This study aims to find scientific evidence about the factors that influence the investment intentions of stock products in Indonesia. The research subjects are stock investors in the Indonesian capital market in 2020. The objects studied include product knowledge, risk perception, influence of society, and investment intentions. The sample was selected by purposive random sampling method. Primary data collection is done online by distributing questionnaires using Google Docs via social media WhatsApp, Telegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…On the other hand, some previous studies (Hamid et al, 2019;Natsir & Arifin, 2021) used motivation in the form of stock returns and additional benefits, while this study found the role of motivation from an Islamic point of view. Syaifullah and Aprianti (2018) found that Motivation has a vital role in influencing the amount of investment interest.…”
Section: Islamic Motivation Affects the Intention Of Sharia Stock Inv...mentioning
confidence: 56%
See 1 more Smart Citation
“…On the other hand, some previous studies (Hamid et al, 2019;Natsir & Arifin, 2021) used motivation in the form of stock returns and additional benefits, while this study found the role of motivation from an Islamic point of view. Syaifullah and Aprianti (2018) found that Motivation has a vital role in influencing the amount of investment interest.…”
Section: Islamic Motivation Affects the Intention Of Sharia Stock Inv...mentioning
confidence: 56%
“…Although initially, respondents said they were interested in investing, it could be that in the middle of their journey, they became Islamic Education and Intention of Sharia Stock Investment in Pandemic COVID-19: … Journal of Accounting and Investment, 2023 | 207 less excited because of the many obstacles faced (Nandar, Rokan, & Ridwan, 2018;Peristiwo, 2016;Rinwantin & Pujiastuti, 2020). On the other hand, some previous studies (Hamid, Mardhiah, & Midesia, 2019;Natsir & Arifin, 2021;Razak, Jannah, & Saleh, 2019) used Motivation in the form of stock returns and other benefits. The low income in the community causes them to be afraid to start investing in the capital market, especially in the Islamic capital market.…”
Section: Introductionmentioning
confidence: 99%
“…Selanjutnya hipotesis yang ditetapkan dalam penelitian ini yaitu: H2: Risiko investasi dapat meningkatkan minat generasi Z membeli sukuk ritel Setiap investor harus menanggung resiko atas investasi yang dilakukannya. Resiko investasi yang timbul tersebut akan memengaruhi minat calon investor dalam melakukan investasi (Natsir & Arifin, 2021;Setiawan et al, 2021;Lestari et al, 2021). Hipotesis selanjutnya yaitu: H3: Literasi keuangan dapat meningkatkan minat generasi Z membeli sukuk ritel Sikap dan perilaku konsumen telah mengalami perubahan yang signifikan sebagai dampak dari pesatnya perkembangan media sosial (Vrontis et al, 2021).…”
unclassified